The Relationship Between Pain and Sleep Quality in Postoperative Patients During Surgical Treatment at Dr. Tadjuddin Chalid General Hospital, Makassar - Muhammad Rias Sukiman; A. Asrina; Haeruddin; A. Muh. Multazam; Nur Ulmy Mahmud; Muh. Khidri Alwi (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
Background: Pain is one of the most common complaints experienced by patients after surgery and can negatively affect sleep quality during the recovery period. Sleep disturbances caused by pain may delay the healing process, increase the risk of complications, and reduce patient comfort. Objective: This study aimed to analyze the relationship between pain intensity and sleep quality among postoperative patients in the surgical ward of Dr. Tadjuddin Chalid General Hospital, Makassar. Methods: This study employed a quantitative research design with a cross-sectional approach. A total of 74 postoperative patients were selected using the Slovin formula. Pain intensity was measured using the Numeric Rating Scale (NRS), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). The data were analyzed using univariate and bivariate analyzes with the Chi-square test. Results: The majority of respondents experienced moderate pain (45.9%) and poor sleep quality (66.2%). The Chi-square test revealed a significant relationship between pain intensity and sleep quality among postoperative patients (p = 0.001). All respondents with severe pain had poor sleep quality, whereas most respondents with mild pain had good sleep quality. Conclusion: There was a significant relationship between pain intensity and sleep quality among postoperative patients. The higher the pain intensity experienced, the poorer the sleep quality. Optimal pain management is an essential component of nursing care to improve sleep quality and support faster recovery in postoperative patients.